2006
DOI: 10.1074/jbc.m508045200
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Phosphorylation of NF-κB p65 at Serine 468 by T Cell Costimulation Is Mediated by IKKϵ

Abstract: Here we identify IKK⑀ as a novel NF-B p65 kinase that mediates inducible phosphorylation of Ser 468 and Ser 536 in response to T cell costimulation. In addition, the kinase activity of IKK⑀ contributes to the control of p65 nuclear uptake. Serines 468 and 536 are evolutionarily conserved, and the surrounding amino acids display sequence homology. Down-regulation of IKK⑀ levels by small interfering RNA does not affect inducible phosphorylation of Ser 536 but largely prevents Ser 468 phosphorylation induced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(98 citation statements)
references
References 48 publications
6
87
1
1
Order By: Relevance
“…With regards to NF-B, IKK⑀ was recently shown to phosphorylate p65 at two of its serine residues (468 and 536) and to control its nuclear import. 28 In summary, the transcriptome profile of IKK⑀ confirms the induction of already described genes and allows depiction of new IKK⑀-induced genes. In particular, these data point out that IRF3-induced genes and genes related to the antiviral action of IFN represent an important fraction of all the genes strongly induced by IKK⑀ ( Table 2).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…With regards to NF-B, IKK⑀ was recently shown to phosphorylate p65 at two of its serine residues (468 and 536) and to control its nuclear import. 28 In summary, the transcriptome profile of IKK⑀ confirms the induction of already described genes and allows depiction of new IKK⑀-induced genes. In particular, these data point out that IRF3-induced genes and genes related to the antiviral action of IFN represent an important fraction of all the genes strongly induced by IKK⑀ ( Table 2).…”
Section: Resultsmentioning
confidence: 86%
“…25 In addition to phosphorylating IRF3 and inducing IFN, IKK⑀ is also known to induce genes through the NF-B and c/EBP␦ transcription factors. [26][27][28] Therefore, to have exhaustive information on the involvement of IKK⑀ in an antiviral action against HCV, we have analyzed its transcriptome profile after provoking its overexpression by transfection in cells expressing an HCV replicon. This revealed several genes involved in translational control, genes involved in apoptosis, and genes of the ISGylation pathway as well as genes from the chemokine family.…”
mentioning
confidence: 99%
“…During the course of this study, Mattioli et al (57), reported that IKK was involved in the phosphorylation of RelA/p65 at Ser 468 in response to T cell costimulation and demonstrated that this phosphorylation primarily affected RelA/p65-dependent transactivation. Thus, the function of IKK -mediated phosphorylation of RelA/p65 appears distinct from the function described here for cRel.…”
Section: Potential (Reviewed In Ref 21) Direct Phosphorylation Of Nf-bmentioning
confidence: 99%
“…The phosphorylation levels of these two sites are dramatically increased upon stimulation of NF-kB activity. 29,30 Moreover, studies show that tumor cell apoptosis induced by anticancer reagents is associated with decreased p65 phosphorylation at Ser536 residue, [31][32][33] suggesting that p65 Ser536 phosphorylation is important for maintaining cancer cell survival and can be inhibited by anticancer reagents. In this study we showed that not only phosphorylation of Ser536 but also phosphorylation of Ser468 is downregulated during HDAC inhibitor-induced apoptosis of EC cells.…”
Section: Discussionmentioning
confidence: 99%